Variation orders in Universiti Teknologi Malaysia (UTM) construction projects - Ibrahim, Nor Hayati (2006)
The project holder have to believe that no construction method or for that matter the project, is free of variation and it’s afterward activity of claims. A document review was done for 18 numbers of construction contract documentation projects in Universiti Teknologi Malaysia (UTM) during the period of the Seventh Malaysian Plan from 1996 to 2000 with the total value of all projects in the excess RM100 million. The client, consultant and contractor become the main respondent target. In general, UTM’s construction projects of building works, renovation works and infrastructure works during Seventh Malaysian Plan are not impervious to variation orders. Every project of building works an average of RM 2.08 million is expend on variation orders and about RM 0.31 million is spent for every variation orders occurred in renovation and infrastructure works. All these have impacted the cost and the completion time of projects. This study has concluded the most numerous cause of variation orders in UTM construction projects which is inadequate consideration of design. Meanwhile, the top five of the effects of these variation orders are listed as followed; increase in project cost; delay in payment; procurement delay; logistic delay; completion schedule delay. The findings of this study also points out that the involvement of profession in the design phase and continuous coordination and direct communication are the two most considered factors to minimizing the happening of variation orders